DEVELOPMENT OF GANODERMA DETECTION AND IMAGING USING ELECTRICAL RESISTANCE TOMOGRAPHY - MOHAMAD SHOFFIAN, MOHAMAD AQIL (Universiti Teknologi PETRONAS, 2017)
Majority of the oil palm plantations in Malaysia are threatened by Ganoderma Basal Stem Rot (BSR) cause by bracket fungus, Ganoderma boninense. Consequently, oil palm yield gradually decrease from 22% up to 45% in fresh fruit bunches (FFB). Therefore, researchers has been looking into industrial process tomography as a reliable tool for imaging. Electrical tomography is the most potential method for realtime imaging tool because of its inherent simplicity and high-speed capabilities. The scheme used for ERT is current-excitation and voltage-measurement and real time cross-sectional images is generating from electrical conductivity distribution in correlation of hollowness inside the tree trunk where the data acquired is used to classify the disease according to Ganoderma Severity Index (GSI) henceforth providing researchers greater platform to prescribe best solution to counter the major pathogen. Then, the lifespan of oil palm can prolong up to 30 years with maximum yield production of fresh fruit bunches (FFB). Consequently, a preliminary system for developing full flesh tomography system has been achieved in this project.